The behavioral effects of CBD and THC in mouse models of psychosis. Issue 8 (August 2019) - Li, C.K.; Mielnik, C.A.; Ramsey, A.J.; Ross, R.A.; Burnham, W.M.
Abstract : Approximately 10% of the patients with long-term temporal-lobe epilepsy develop psychotic symptoms, which are known as the "psychosis of epilepsy" (POE). The relationship between the two disorders remains elusive, although they are believed to share similarities in underlying mechanisms and substrates. Previous studies have reported anti-psychotic properties of cannabidiol (CBD) and pro-psychotic properties of Δ 9-tetrahydrocannabinol (THC) in both animals and human patients. The present study investigated the behavioral effects of CBD (60 and 120 mg/kg), THC (4 mg/kg) and a combination of CBD and THC at a 15:1 ratio (60:4 mg/kg) in two mouse models of psychosis – GluN1KD and DATKO mice. The open field locomotion test (OFT) and the pre-pulse inhibition test (PPI) were used. In the OFT, CBD had no significant effect in either mouse model, whereas THC significantly decreased locomotion in both models, (accompanied by an observed impairment in ambulation). In combination, CBD increased THC's effects in GluN1KD mice and decreased THC's effects in DATKO mice. In the PPI test, 120 mg/kg of CBD significantly improved PPI in GluN1KD mice. Testing in DATKO mice is still in progress. The behavioral impairments seen in the two mouse models are consistent with other animal models of psychosis. The effects of CBD and THC, however, do not match the prior literature. The cannabinoids used in this work were donated by MedReleaf (Markham, ON). This study was supported in part by EpLink – The Epilepsy Research Program of the Ontario Brain Institute.